Analysis of Financial Education, Risk Management, and Accessibility of Technology-Based Loans on Improving Village Economic Resilience - Soraya Lestari; Muksalmina Muksalmina; Baiti Baiti; Salwa Hayati Hasan; Sari Raudhatul Jannah SI (Graha Primera Saintifika, 2026)
Village economic resilience is critical for sustainable rural development, yet remains challenged by limited financial literacy, inadequate risk management, and restricted access to capital. This study examines how financial education, risk management, and technology-based loan accessibility influence economic resilience among culinary sector MSMEs in Syiah Kuala District, Banda Aceh. Using a quantitative approach, data were collected through Likert-scale questionnaires distributed to 68 respondents selected via proportional stratified random sampling from 217 culinary MSMEs. Multiple linear regression analysis reveals that all three independent variables significantly and positively affect village economic resilience. Technology-based loan accessibility emerged as the most dominant factor, followed by financial education and risk management. The findings suggest that integrated interventions combining digital financial inclusion, financial literacy programs, and risk management training can substantially strengthen rural economic resilience. This research contributes empirical evidence on the synergistic effects of these factors in developing economies and provides actionable insights for policymakers designing resilient rural economic development strategies. From a policy perspective, the findings highlight the importance of integrated rural economic policies that simultaneously promote financial education, strengthen risk management capacity, and expand responsible access to technology-based lending. Policymakers and local governments are encouraged to design village-level financial literacy programs and fintech regulations that support productive MSME financing while minimizing financial vulnerability.